The Use of Medicinal Plant Species by the Temuan Tribe of Ayer Hitam Forest, Selangor, Peninsular Malaysia - Ibrahim, Faridah Hanum; Hamzah, Nurulhuda (Universiti Putra Malaysia Press, 1999)
Preliminary results of a study on the use of medicinal plant species by the indigenous people from the Temuan tribe at Ayer Hitam Forest are presented. Although this forest is surrounded by rapid socio-economic development, it is ironically a substantial pharmacopoeia for the Temuans. A total of 98 plant species with 140 different uses were recorded and they were grouped into seven methods of application namely drink, eat, chew, poultice, rub, bath and shampoo.